A Story of Institutional Misfit: Congress and US Economic Sanctions1. Issue 4 (15th August 2013) - Hatipoglu, Emre
Abstract : Parting from conventional studies on economic sanctions that look at the properties of the targeted state, this study focuses on the institutional origins of economic sanctions. I observe that most US sanctions either originate from the legislative or the executive branch. Building on this observation, I argue and present evidence that the institutional origin of a US sanction has a discernible effect on that sanction's duration. An institutional approach underpins the theory I develop to explain this difference. The veto‐point approach focuses on the institutional inertia bestowed upon foreign policy actions executed through law and suggests that sanctions imposed as law should last longer than those carried out by executive order. Semi‐parametric duration analysis conducted on the recently released Threat and Imposition of Economic Sanctions data confirms this expectation.